Comparison of personality traits in different cultures : are there differences beetween Icelandic and Serbian young adults? - Nikolić, Lazar, 1995- (2022)
Studies have shown that there are differences in personality traits between countries. Prior studies showed that Icelanders scored lower in personality traits such as extraversion, openness to experience and agreeableness. Serbians scored higher in personality traits extraversion and openness to experience. This shows that the difference in personality traits between these countries exists. However, there has never been done direct comparison between Iceland and Serbia. This study did a comparison between countries of Iceland and Serbia in personality traits HEXACO-100. The aim was to see if there were any differences or similarities between and within countries. To assess whether there was a correlation between countries and personality traits HEXACO-100, Pearson’s r correlations were used. Also, binary logistic regression was used to see the prediction between personality traits and countries. The sample consisted of 60 participants, aged 18-30 years old. The results showed medium correlation between countries and personality traits. Age group has shown no Pearson’s correlation to any of the personality traits in neither country. There were differences for genders, females from Serbia scored higher in emotionality and agreeableness than females from Iceland. Age group 18-24 from Iceland scored higher on honesty-humility than the same group from Serbia. The results of this study suggest that there are differences and similarities in personality traits HEXACO-100 between Iceland and Serbia in gender and age groups, but more studies are needed with a larger sample. Keywords: Personality traits, HEXACO-100, Iceland, Serbia, differences Rannsóknir hafa sýnt að það er munur á persónuleikaþáttum milli landa. Fyrri rannsóknir sýndu að Íslendingar skoruðu lægra í persónuleikaþáttum eins og úthverfu, viðsýni og samvinnuþýði. Serbar skoruðu hærra í persónuleikaþáttunum úthverfu og viðsýni. Þetta sýnir að það sé munur á persónuleikaþáttum milli þessara landa. Hins vegar, hefur aldrei verið gerður beinn samanburður á ...